POLA KATA JAMA’ TAKSĪR DALAM NOVEL “QĀTILU HAMZAH” KARYA NAJIB KAILANI (ANALISIS MORFOSINTAKSIS - Dena Agustina; Yoyo Yoyo; Mat Taib bin Pa (Universitas Muhammadiyah Gorontalo, 2021)
This study aims to describe the word patterns of jama 'takṡīr, grammatical signs, and their function and position in the novel